Adoption of Network Governance in Indonesia’s anti-corruption movement: A case study of GNPSDA - Sarah Azzahwa (Integritas: Jurnal Antikorupsi, 2025)
This research investigates the adoption and discontinuation of the Network Governance (NG) model as an anti-corruption strategy in Indonesia’s natural resource sector. It responds to a gap in existing research and studies that insufficiently explains the rationale behind adopting NG models and poorly explores the reasons for the failure of this model to persist. This study uses the National Movement of Saving Indonesia’s Natural Resources (GNPSDA) as its case study, a program which was initiated by the Corruption Eradication Commission (KPK-RI) in 2013. A qualitative case study design was employed to explore both the driving factors and barriers that shaped the initiative, involving ten semi-structured interviews with KPK-RI’s officials and non-governmental organization (NGO) representatives. The findings reveal two internal drivers—limitations of conventional anti-corruption methods and legal mandates for public participation—and three external drivers, namely international pressure, issue complexity, and cross-sectoral alignment. Despite early achievements, the GNPSDA dissolved in 2019 due to four interrelated challenges: poor coordination among stakeholders, political pressure from oligarchs, lack of consistent leadership support, and the absence of a structured succession plan. This research contributes to the literature on network governance and anti-corruption by providing actionable insights for sustaining collaborative reform initiatives in complex governance landscapes.